Environmental Communication and Community Empowerment in CSR-based Refuse-Derived Fuel (RDF) Production: A Case Study in Cirebon, Indonesia - Afnan, Dikhorir; Perwira, Evan Hakeem; Irfan, Agus; Kamaluddin, Muhammad (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Inadequate waste management in rural areas significantly contributes to environmental degradation owing to limited infrastructure and low public awareness. This study addresses a critical gap in RDF research, which has largely emphasized technical feasibility while overlooking social empowerment and institutional challenges. A qualitative case study was conducted in three villages in Cirebon Regency, Indonesia, supported by descriptive quantitative analysis. Data collection included interviews, focus group discussions, field observations, and document reviews, with NVivo software used for coding and triangulation. The findings demonstrate that participatory training, decentralized waste sorting, and incentive-based schemes enhanced household waste behavior and doubled RDF output in 2023. However, persistent gendered inequalities, lack of legal status for waste units, and weak stakeholder coordination undermined long-term sustainability. This study contributes to environmental communication and empowerment scholarship by demonstrating how inclusive governance and institutional reform determine the success of waste-to-energy programs. Practically, the results provide policy guidance for CSR-based initiatives, emphasizing gender equity, participatory monitoring, and transparent financing as prerequisites for sustainable RDF governance.